Rapid evidence profile #67: Identifying what is known about the health-system arrangements that can support the delivery of innovative models of home care - Bain, T; DeMaio, P; Ahmednur, A; Bhuiya, AR; Alam, S; Moat, KA (My University, 2024)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the health-system arrangements that can support the delivery of innovative models of home care in response to a decision-maker’s request.
Keywords: health-system; delivery; models; home care